1975
DOI: 10.1104/pp.55.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Availability in Polyethylene Glycol Solutions and Its Implications in Plant-Water Relations

Abstract: The solubility of 02 in polyethylene glycol 4000 and 6000 solutions of varying concentrations was determined iodimetrically (titrimetrically) and electrochemically using a rotating glassy carbon electrode and a PAR Model 174 Polarograph.The titrimetric determination resulted in the formation of an unexpected precipitate at 2% (w/v) polyethylene glycol corresponding to the approximate critical micelie concentration of the two polyethylene glycol homologs. Beyond 5% polyethylene glycol, 02 concentration was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
10

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(104 citation statements)
references
References 24 publications
3
91
0
10
Order By: Relevance
“…ABA is a regulator of water deficit responses, is a signal during pathogen defence and has a role during low-oxygen stress (Chandler and Robertson, 1994). PEG imposes osmotic stress but probably also affects root respiration (Mexal et al, 1975;Michel and Kaufman, 1973). Further analysis showed that water deficit conditions such as gradual drying, osmotic stress, salt stress and cold ( Figure 5a) triggered a root-specific PPDK induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABA is a regulator of water deficit responses, is a signal during pathogen defence and has a role during low-oxygen stress (Chandler and Robertson, 1994). PEG imposes osmotic stress but probably also affects root respiration (Mexal et al, 1975;Michel and Kaufman, 1973). Further analysis showed that water deficit conditions such as gradual drying, osmotic stress, salt stress and cold ( Figure 5a) triggered a root-specific PPDK induction.…”
Section: Discussionmentioning
confidence: 99%
“…9). PEG causes osmotic stress (Michel and Kaufman, 1973), but can also impose other adverse conditions (Greenway and Munns, 1980) that possibly affect root respiration (Mexal et al, 1975). A complete submergence of rice seedlings for 60 h was also found to induce an accumulation of the 97 kDa protein in roots (Figure 1,no.…”
Section: Aba and Environmental Stresses Induce Ppdk In Roots Of Ricementioning
confidence: 93%
“…First, oxygen status measured inside elongating root tip tissues by Verslues et al (1998) was not reduced by PEG 8000. Second, Mexal et al (1975), who first suggested that roots in PEG might become oxygen limited, also found that the diffusion coefficient of oxygen was similar in water or PEG 6000 solutions. Third, any physiologically significant oxygen deficiency under water deficit would be expected to inhibit respiration-dependent growth in the metabolically active cells 0 to 3 mm behind the root tip in the same way as in other regions of the elongation zone, but this did not occur.…”
Section: Discussionmentioning
confidence: 99%
“…Osmotic solutions require continuous aeration and a large volume of priming solution is required per quantity of seed. As well as this, the use of high concentrations of PEG in solution has low oxygen solubility and diffusivity (Mexal et al 1975). These aspects complicate the priming process and will need to be overcome if priming of beetroot seed is to become a commercial reality.…”
Section: Control Of the Soilborne Pathogens Of Beet Pre-planting Treamentioning
confidence: 99%